2018
DOI: 10.1177/0194599818758020
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Times in Salivary Gland Cancer: National Patterns and Association with Survival

Abstract: Objective To characterize treatment times in salivary cancer; associate treatment times with patient, tumor, and treatment characteristics; and examine the association of treatment times and overall survival. Study Design Retrospective cohort. Setting Commission-on-Cancer Accredited Hospitals 2004-2013. Subjects and Methods In total, 5953 patients with salivary cancer included in the National Cancer Database were identified. For each treatment interval, patients in the fourth quartile ("prolonged") were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 43 publications
(118 reference statements)
9
47
3
Order By: Relevance
“…However, facilities with higher volumes of SNSCC were associated with decreased risk of positive margins, likely a result of increased anatomic familiarity and multidisciplinary teams that can better inform surgical technique . This bolsters evidence from previous studies demonstrating favorable prognostic factors for head and neck cancer when treated at HVFs and academic centers, as has been seen in many other head and neck cancer subsites …”
Section: Discussionsupporting
confidence: 57%
“…However, facilities with higher volumes of SNSCC were associated with decreased risk of positive margins, likely a result of increased anatomic familiarity and multidisciplinary teams that can better inform surgical technique . This bolsters evidence from previous studies demonstrating favorable prognostic factors for head and neck cancer when treated at HVFs and academic centers, as has been seen in many other head and neck cancer subsites …”
Section: Discussionsupporting
confidence: 57%
“…Of the multiple factors that may underlie prolonged DTS, care transitions appear to play a major role in sinonasal cancer. Patients in our study more commonly received treatment at a site other than the diagnosing facility (61%) compared to studies of salivary (33%), laryngeal (39%), or hypopharyngeal (43%) cancer using the same database. Such care transitions were among the strongest predictors of prolonged DTS.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment delay is associated with decreased disease control and survival, potentially driven by cancer stage progression or tumor cell repopulation after surgery prolonged treatment times . Although recent studies have analyzed treatment intervals for several different head and neck subsites, the impact of treatment delays in sinonasal cancer has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the delay of thyroid surgery is often safely delayed until after delivery in pregnant patients without compromising oncologic outcomes 40 . Among salivary cancer (all histologies and grades), a national retrospective review found that TTI had no impact on 5‐year overall survival 41 …”
Section: Criteria For Prioritizing Patients Requiring Head and Neck Smentioning
confidence: 99%